IT skills in vocational training curricula and labour market outcomes. Issue 6 (3rd October 2022) - Kiener, Fabienne; Gnehm, Ann-Sophie; Clematide, Simon; Backes-Gellner, Uschi
ABSTRACT: We use vocational training curricula to investigate how IT skills are trained within broader skills packages and how these relate to labour market outcomes. Skills packages are the typical combinations of IT skills (e.g., CNC) and technical or nontechnical skills (e.g., material sciences or work safety) that are jointly required in the real world and occur in training curricula. This broadened perspective of teaching IT skills offers new insights into how digital skills can be successfully integrated into future education and training programmes. We use legally binding vocational education and training (VET) curricula of dual apprenticeship training in Switzerland. We apply natural language processing methods to analyse the extensive curriculum texts, which meticulously define the skills that have to be taught. We identify four typical skills packages, each of which are centred around one of four different types of IT skill (CNC/CAD, control technologies, system technologies, IT-applications). Our empirical analyses show that VET graduates trained in these skills packages receive positive labour market outcomes compared to VET graduates without these skills packages. Moreover, we find that the positive outcomes are not just driven by differences in cognitive skill requirements of the respective occupations.